The Impacts of Two Revisions of the China’s Environmental Protection Fee on Firm Performance: Evidence From Stock Markets - Zheng, Huan; He, Yu (Frontiers in Environmental Science, 2021)
This comparative study aims to investigate how China’s environmental protection fee affected firm performance in two separate sample periods, namely 2001-2006 and 2012-2017, as this policy was revised twice in 2003 and 2014. With the Difference-in-Differences (DID) estimation, we find that the second revision of environmental protection fee had a negative impact on heavy polluting firms, while the influence of the first revision seemed to be insignificant. Moreover, the environmental protection fee had a limited impact on other firms, implying that such a policy had achieved its designed effect by precisely governing heavy polluters. Besides, our additional tests show that the environmental protection fee had stronger impacts on non-connected firms and non-SOEs than politically connected firms and SOEs. Our results are robust to various potential endogeneity issues.